Prevalence of Multidrug-Resistant Salmonella spp. in Asia: A Mini-Review - Salvador, Lara Julia R.; Intengan, Leanne Wilfrede D.; Castillo, Lheean Aira G.; Baluyut, Allyssa Dale D.; Camarao, Maria Ellaine Mae C.; Rueda, Ariane De D.; Baligod, Blessed Joy B.; Go, Champagne P.; Lirio, Mary Rose F. (Asian Journal of Biological and Life Sciences)
Salmonella is a known causative agent for food poisoning across the world with thousands of cases reported annually. The surging multidrug-resistant Salmonella was also evident throughout the decade, worsening the situation and making it an even more crucial public health burden. This paper aims to raise public health awareness on the rapid progression of Salmonella infection resulting from proliferating antimicrobial resistance in different Asian regions. A total of 50 articles extracted from Google Scholar, PubMed, NCBI, and ScienceDirect were included in this review. The prevalent Salmonella serotype and antibiotic that most isolates have built resistance to were identified per Asian region. Overall, Salmonella Typhi is identified as the most isolated typhoidal Salmonella strain while Salmonella Typhimurium is the prevalent NTS strain in Asia. Tetracycline is revealed to have the highest percentage of resistance among all isolated Salmonella spp. in conducted Asian studies. Alarming tetracycline resistance was observed in 11 out of 38 countries incorporated in this mini-review, this is due to chromosomal mutation and ribosomal binding site mutation. Most Salmonella isolates have inherited genetic elements with tetracycline-specific resistant genes, increasing the intrinsic mechanism for antimicrobial resistance. Following tetracycline, significant resistance against nalidixic acid and ampicillin was also observed. Thus, it is highly suggested for public health officials focus on improving the sanitary conditions in food production and processing together with water management safety to address the problem with Salmonella.
Keywords: Antibiotics; Asia; Multidrug-Resistant; Non-typhoidal; Salmonella; Typhoidal.